Pengaruh Suplementasi Ekstrak Ikan Gabus (Channa Striata ) Terhadap Kadar Albumin, Kolesterol, Waktu Remisi Dan Kejadian Relaps Pada Anak Sindrom Nefrotik - Muhammad Heru Muryawan; Ag Soemantri; Hertanto Wahyu Subagio; Nanan Sekarwana (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Background : Nephrotic syndrome (NS) is common in children with massive proteinuria causing severe hypoalbuminemia and hypercholesterolemia. Various attempts are required to increase albunin serum, accelerate remission time, and prevent relapse in order to reduce kidney damage. The Channa striata extract is known for its benefits in increasing albumin levels. Objective : To prove channa striata extract supplementation effect in increasing albumin serum, reducing cholesterol serum, remission and relapse time in children with NS. Methods :This is a double blind randomized controlled trial pre and post test design, 60 children with NS aged 1-15 years were included. A total of 500 mg / day channa striata extract capsule supplementation were administrated 2x1 to the treatment group for 21 days, meanwhile control group received placebo. Children with other chronic disease and with steroid resistance NS were excluded. The outcomes were serum albumin, cholesterol levels, remission and relapse time. Analysis data of albumin and cholesterol was performed by using unpaired t test and Mann-Whitney test. Remission and relapse times were analyzed by chi-square test. Results: There are 60 children met the inclusion criteria (32 children received Channa extract and 28 children were given placebo). Increased albumin level after supplementation was 3,6+0.8 g/dL(p<0.05) higher compared to placebo group 3,2+0.8 g/dL( p<0.05). Decreased levels of total cholesterol between the two groups were not significant (p>0.05). The treatment group remission time was 8.4+2.9 days, 11.0+3.7 day faster compared to placebo group (p <0.05). Relapse in the treatment group (21.4%) were similar to the placebo group (21.9%) (p> 0.05). Conclusions: Channa striata extract supplementation 3x500 mg/day for 21 days is effective to increase albumin levels and accelerate remission time significantly. Decreased cholesterol serum and relapse were not significant. Keywords: nephrotic syndrome, channa striata extract, albumin, cholesterol, remission time, relapse Latar Belakang: Sindrom nefrotik (SN) banyak dijumpai pada anak dengan proteinuria masif yang menyebabkan hipoalbuminemia berat dan hiperkolesterolemia. Diperlukan upaya meningkatkan kadar albumin, mempercepat waktu remisi dan mencegah relaps guna mengurangi kerusakan ginjal. Ekstrak ikan gabus (EIG)/Channa striata) diketahui dapat meningkatkan kadar albumin. Tujuan: Membuktikan pengaruh suplementasi EIG terhadap peningkatan kadar albumin, penurunan kolesterol,waktu remisi dan kejadian relaps pada anak SN. Metode: Penelitian randomized controlled trial pre and post test design, tersamar ganda, dilakukan mulai Maret-November 2017 terhadap 70 anak SN usia 1-15 tahun, terbagi menjadi 35 anak kelompok suplementasi EIG 2x500 mg/hari selama 21 hari; 35 anak kelompok kontrol. Anak dengan penyakit kronis lain, anak dengan resisten steroid di eksklusi. Luaran yang diteliti adalah kadar albumin, kolesterol, waktu remisi dan kejadian relaps. Analisis data kadar albumin dan kolesterol dengan uji t tidak berpasangan dan uji Mann-Whitney, waktu remisi dan kejadian relaps dengan uji Chi-Square. Hasil: Enam puluh subyek masuk kriteria penelitian (32 di kelompok EIG dan 28 di kelompok plasebo). Peningkatan kadar albumin setelah pemberian EIG 3,6+0,8 g/dL lebih tinggi dibanding kontrol 3,2+0,8 g/dL (p<0,05). Penurunan kadar kolesterol total diantara dua kelompok didapatkan nilai p>0,05. Waktu remisi kelompok EIG 8,4+2,9 hari, lebih cepat dibanding kontrol 11,0+3,7 hari (p<0,05). Kejadian relaps kelompok EIG (21,4%) sama dengan kontrol (21,9%) (p>0,05). Kesimpulan: Suplementasi EIG 2x500 mg/hari selama 21 hari, efektif meningkatkan kadar albumin dan mempercepat waktu remisi secara bermakna. Penurunan kadar kolesterol dan kejadian relaps tidak bermakna. Kata kunci: sindrom nefrotik, ekstrak ikan gabus, albumin, kolesterol, waktu remisi, relaps